The desert city: in what sense? An approach to the concept - Talha, Bachir (Journal of Architecture and environment of child, 2021)
The present intervention aims to shed the light on the meaning of the desert city, by searching for the variables controlling the formulation of the concept. Urbanization constitutes the most important variable; however, this does not deny the existence of other variables that cannot be neglected or overlooked as they have the same importance in determining the features of the desert city, and they are related to social, historical and cultural contexts in many cases. Therefore, the present intervention gives these variables their value by highlighting them and underlining their role, and all this by referring to several approaches which belong to different fields of knowledge that the desert city constituted the focus of their work. This intervention also employs the intellectual heritage produced around the desert city and seeks to reach a sound formulation in line with the cultural and civilizational peculiarities in which the desert city was established.